The electron as a probe to measure the thickness distributions of electroactive films. Issue 4 (29th November 2019) - Buesen, Darren; Li, Huaiguang; Plumeré, Nicolas
Abstract : A theoretical model combined to an experimental study shows that the morphology of electron conducting films can be quantified directly from the analysis of cyclic voltammetry data. Abstract : Electron conducting films are ubiquitous in applications such as energy conversion, and their ability to fulfill their catalytic function can be greatly limited by inhomogeneities in their thickness or breaks within the film. Knowing the electroactive film thickness distribution would greatly facilitate optimization efforts, but techniques to measure this are lacking. Here, we present an electroanalytical method that provides the thickness distribution of the electrochemically accessible fraction of redox-active films in which the transfer of electrons is diffusional, i.e. by electron hopping. In this method, as the time scale of the experiment (the scan rate) is changed, the location of the diffusion layer boundary relative to the film roughness features is varied, allowing for the extraction of the film thickness distribution. In addition to being conveniently carried out in the solvated state, which is often the operational state of these conductive films, this approach is highly complementary to classical microscopy methods since it samples the entire modified electrode and is specific to the electroactive portions of the film. Therefore, this approach provides information on film morphology that is truly relevant for the catalytic processes being optimized, and thus can guide the optimization of catalyst integration in films towards macroscale cohesion and thickness homogeneity which are essential for optimal performances.